Feelings and expectations experienced by teenagers to become mothers: introductory note - Jéssica Rodrigues Silveira; Luiza Cremonese; Laís Antunes Wilhelm; Lisie Alende Prates; Gabriela Oliveira; Lúcia Beatriz Ressel (Universidade Federal de Santa Maria, 2017)
Aim: to know the feelings and expectations experienced by adolescent women to become mothers. Method: descriptive, field study with a qualitative approach. The study will be at a hospital in the interior of Rio Grande do Sul. The subject of research will be teenagers in the postpartum period melican. The data will be collected by means of a semi-structured interview, from October to November 2016, and, then, analyzed through the operational proposal of Minayo. Expected results: it is expected that this study promotes discussions and reflections that help in the understanding the feelings and expectations experienced by young teenagers to become mothers